Neuroleadership and Its Role in Educational Settings: A Review of Current Practices - Antonopoulou, Hera (Technium Education and Humanities, 2024)
This paper provides an overview of neuroleadership and its application in educational settings toward effective leadership and student outcomes. Neuroleadership combines the emerging research in neuroscience with theories of leadership, aiming at understanding the neural processes that influence decision-making, motivation, emotional intelligence, and managing change in educational contexts. As a study, it highlights possible benefits that could emerge from the application of neuroscientific principles for improving teacher-student relationships through the creation of adaptive learning environments and fostering growth among students via neural plasticity. It also highlights strategies such as emotional self-regulation, collaborative thinking, and mindfulness, which may be used in the development of enhanced well-being and good leadership practices among educators and students. The paper calls for professional development linked to principles of neuroleadership and for more case studies to explore applications in practice. It also gives emerging technologies such as neurofeedback, AI tools, and VR environments for enhancing educational leadership and a better learning experience. Overall, the study epitomizes the potential of neuroleadership in transforming practices in educational settings and linking it with future-oriented professional development.